Impact of Work from Home on Work Stress Symptoms in Employees X of North Sulawesi Province - I Wayan Gede Suarjana; Suehartono Syam; Bastian Rikardo Parhusip; Richard Andreas Palilingan; Dewo Agung Nugroho Narosaputra; Siti Fathimah; Anne Indiarti Banjar Nahor (GoAcademica Research & Publishing, 2022)
Work stress is an imbalance of task demands with a person's work ability that creates tension through physical and emotional responses. The purpose of this study was to find out the impact of Work from Home on the symptoms of worker work stress. The research method used is quantitatively descriptive with cross-sectional design. The sample in this study was 63 employees who had filled out research instruments. The research intrusion used is an online questionnaire filled out through Google Form through the WhatsApp Group platform. Variable Work from Home uses two indicators, namely the work environment factor and workload. Using a statistical analysis of multiple linear regression statistics, researchers stated that the work environment had no significant effect on employee work stress symptoms and that work had a positive and significant effect on employee work stress symptoms during Work from Home.